School staff advice-seeking patterns regarding support for vulnerable students. Issue 2 (10th December 2019) - Ortega, Lorena; Thompson, Ian; Daniels, Harry
Abstract : Purpose: Supporting the learning and wellbeing of vulnerable students is an important yet challenging part of school educators' work. The purpose of this paper is to investigate advice-seeking patterns around the issue of supporting the learning and wellbeing of vulnerable students, among professional staff in six English secondary schools. The paper focuses on investigating variation in advice-seeking patterns among schools, exploring the association between these patterns and staff perceptions of the school climate for collaboration, and examining how these informal advice-seeking patterns relate to formal support arrangements in the schools. Design/methodology/approach: A mixed-methods approach that combined findings from social network analysis with in-depth interviews was used. Findings: It was found that advice-seeking patterns among staff vary substantively, even among similar schools. Furthermore, schools with more cohesive and reciprocal advice networks also showed a stronger climate for collaboration (i.e. mutual respect and distributed leadership). Also, formal organizational structures and informal advice-seeking structures showed coherence in the sample, as formally designated leaders, such as the Headteacher and the Special Educational Needs Coordinators, were generally highly central to their schools' advice network. Originality/value: This study advances the field as there is little research that examines the social networks of educators in England, and no previous studies that explore teacher advice-seeking networks in relation to supporting vulnerable students, internationally.